Effect of Protists on Horizontal Transfer of Antimicrobial Resistance Genes in Water Environment - Satoru Suzuki; Daisuke Sano (Journal of Water and Environment Technology, 2023)

(untitled)
There is much evidence that the environment is a reservoir of antibiotic resistance genes (ARGs). For ARG latency and stability, environmental factors should play a role since ARGs are transferred among bacterial species, which results in their evolution and dissemination. Recent findings have expanded the novel mechanisms of horizontal gene transfer (HGT) beyond classically accepted HGT mechanisms such as conjugation, transformation, and transduction. In these HGT processes, environmental factors directly or indirectly affect the transfer rate and mechanism. Here, we focus on the effect of protists that affect HGT, because HGT is regulated among the microbial community, in which protist grazing is one factor that enhances HGT. Protist grazing eliminates planktonic bacteria. However, it is reported that environmental DNA release and HGT in protist vacuoles are increased by the grazing, although the effect is not uniform and depends on the environmental conditions. Biofilms protect bacteria and accelerate HGT. In these processes, quorum sensing and organic matter contribute to HGT. Although HGT occurs between bacterial cells, other microorganisms such as protists should be recognized as factors relating to HGT. We should pay attention to microbial ecosystem when consider ARG risk from water environment in terms of “one health” aspect.